Manajemen Pendidikan untuk Pondok Pesantren - Ahmad Janan Asifudin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
Visionary is the most important character which should be possessed by Kiai, the leader of pesantren, to be ideal manager. This also applies for those who constitute the Kiai’s assistants. A pesantren led by this type of Kiai will be enlightened and considerably motivated to achieve clear long term objectives and planning. For instance, the best Islamic education system concept is pesantren with its ideal madrasah. Moreover, generally pesantren has its own feature in which the entire elements reside within the pesantren constantly obey the existing procedures. This has emerged as the result of strong obedience culture toward the Kiai who owns the greatest authority inside the pesantren and its surrounding environment. However the level of obedience will vary according to ‘government system’ implemented by each pesantren. Those pesantren also employ different strategies in their education system.